Postnatal metformin treatment alters rat Sertoli cell proliferation and daily sperm production. (9th February 2021) - Rindone, Gustavo Marcelo; Gorga, Agostina; Pellizzari, Eliana Herminia; Camberos, María del Carmen; Galardo, María Noel; Da Ros, Vanina Gabriela; Buffone, Mariano Gabriel; Meroni, Silvina Beatriz; Riera, María Fernanda
Abstract: Background: The direct correlation between Sertoli cell number and sperm production capacity highlights the importance of deciphering external factors that modify Sertoli cell proliferation. A growing body of evidence in vitro suggests that metformin, the main pharmacological agent for type 2 diabetes treatment in children, exerts anti‐proliferative effects on Sertoli cells. Objective: The aims of this study were to investigate the effect of metformin administration during postnatal period on Sertoli cell proliferation and on cell cycle regulators expression and to analyze the impact of this treatment on the sperm production capacity in adulthood. Materials and Methods: Sprague Dawley rat pups were randomly divided into two groups: MET (receiving daily 200 mg/kg metformin, from Pnd3 to Pnd7 inclusive) and control (receiving vehicle). BrdU incorporation was measured to assess proliferation. Gene expression analyses were performed in Sertoli cells isolated from animals of both groups. Daily sperm production and sperm parameters were measured in adult male rats (Pnd90) that received neonatal treatment. Results: MET group exhibited a significant decrease in BrdU incorporation in Sertoli cells. Concordantly, MET group showed a reduction in cyclin D1 and E2 expression and an increase in p21 expression in Sertoli cells. In addition, metformin‐treated animals displayed lower values of daily sperm production on Pnd90. Discussion and Conclusion: These results suggest that metformin treatment may lead to a decrease in Sertoli cell proliferation, a concomitant altered expression of cell cycle regulators and ultimately, a reduction in daily sperm production in adult animals.